Pemanfaatan Game Musik sebagai Media Edukasi: Studi Kualitatif tentang Peningkatan Fungsi Kognitif dan Koordinasi Visual-Auditori pada Pemain Game Hatsune Miku: Colourful Stage! - Anselia Lie; Shakti Velen; Risa Audina; Desi Sefriyani; Samuel Jonnatan Aprilianov Tambunan (Asosiasi Dosen Muda Indonesia, 2026)
ABSTRACT The development of video games in today's digital ecosystem shows a shift in function from being merely a medium of entertainment to a medium with educational potential. One genre that is interesting to study is music games, as they combine visual and auditory stimuli with motor responses in an integrated manner. This study aims to analyze the use of the music game Hatsune Miku: Colorful Stage! as an alternative educational medium in improving cognitive function and visual-auditory coordination in music game players. This study uses a qualitative method with a case study approach. There were ten research subjects aged 18–19 years, divided into two groups: music game players and non-music game players. Data collection techniques were carried out through observation and the administration of simple and non-standard cognitive tasks, including short-term memory tests, attention control tests, problem-solving tests, and simple arithmetic tests. The data were analyzed using the Miles and Huberman model through data reduction, data presentation, and descriptive conclusion drawing. The results showed that music game players tended to have more stable working memory, attention control, cognitive flexibility, and information processing speed than non-players. These findings indicate that music games not only serve as a means of entertainment but also have the potential as an educational medium that can be used to train cognitive functions and visual-auditory coordination, especially in the late adolescent age group.